Effect of Nutrients on Cognitive Function during Childhood to Adolescence: A Review - Sehjpal, Ankita; Sanghi, Divya (International Journal of Child Health and Nutrition, 2025)
Background: Cognitive functioning and development include making decisions, processing information, and responding properly to the environment. People with healthy brains can identify their skills and modify their cognitive, mental, emotional, and behavioral functions to cope as best they can with various life situations. Methods: Studies from the last 15 years included from various search engines like Google Scholar, Pubmed, Science Direct, Scopus Result: The health of the brain is affected by many situations, including illnesses, injuries, mood disorders, substance addiction, and aging-related changes in the brain. There is evidence of numerous changeable lifestyle factors, even though some cannot be changed: Food and exercise, social interaction and mental activity, as well as alcohol and tobacco use, can all help stabilize or enhance deteriorating cognitive performance. Conclusion: Each macronutrient and micronutrient plays a critical role in supporting cognitive function, and their combined effects may be synergistic due to the interrelated nature of their physiological and biochemical actions.